Case report: Nephrotic syndrome induced by Lenvatinib treatment in a patient with von Hippel-Lindau syndrome - Shuyu Zhang; Yuehong Li; Wen Wen (BMC Nephrology)
Abstract Von Hippel-Lindau (VHL) syndrome is an autosomal dominant hereditary disease characterized with mutiple organ tumors. Tyrosine kinase inhibitor (TKI) is one of the targetd treatment for VHL syndrome. Lenvatinib (LEN), an oral small-molecule multiple TKI, and proteinuria is one of the most common adverse events associated with LEN. We reported a case of lenvatinib-induced nephrotic syndrome in a Chinese patient with VHL syndrome. The renal biopsy was proved with thrombotic microangiopathy (TMA) and focal segmental glomerulosclerosis (FSGS)-like pattern. Drug-induced kidney injury deserves further attention.